An ugly truth : inside Facebook's battle for domination - Frenkel, Sheera (The Bridge Street Press, 2021)
"Once one of Silicon Valley's greatest success stories, Facebook has been under constant fire for the past five years, roiled by controversies and crises. It turns out that while the tech giant was connecting the world, they were also mishandling users' data, spreading fake news, and amplifying dangerous, polarizing hate speech ... Drawing on their unrivaled sources, Sheera Frenkel and Cecilia Kang take readers inside the complex court politics, alliances and rivalries within the company to shine a light on the fatal cracks in the architecture of the tech behemoth"--Publisher's description.